Hybridity Culture: The Adaptive Reuse Concept for an Escape Place. Study Case: Gedung Antara, Pasar Baru, Jakarta. Issue 1 (November 2021) - Fajarwati, A A S; Rombe, O SC; Henry, L; Rachmayanti, I; Meliana, S
Abstract: The growth of cities has an impact on society. As a result of the population's increased bustle and activity needs, dwelling space is becoming increasingly limited. The concept of "third place in hybrid and multicultural areas" is explored in this study, which combines adaptive reuse in buildings with the idea of multicultural hybridity. By adapting historic structures into new purposes that meet current needs, we could solve escaping spaces. To put that concept into practice, we must first comprehend the region's cultural characteristics. The heritage building in Pasar Baru is situated in an area generated by the complex hybridity of Jakarta's numerous ethnic communities. This area's hybridity offers an exciting place that can be used as an escape route. This study employs a qualitative research approach that includes in-depth observations in Pasar Baru. We study old buildings that have a hybrid character from the ethnicities prevalent in Pasar Baru. According to the findings, heritage structures undergoing adaptive reuse must be evaluated regularly to account for changes in spatial conditions that occur over time. Adaptive reuse transforms ancient structures into new roles in conservation and uses a cultural context approach in the surrounding area, allowing for more efficient service.